Foundations of British monetary policy - Artis, Michael J. (New York : A.M. Kelly, 1965)
The book is concerned with the development of those fundamental relationships upon which are based the authority and ability of the Bank of England to initiate and implement monetary policy. Such as the financial system, Government, the corpus of legislation affecting it, and the internal changes that have taken place inside the Bank itself.
Reprints of economic classics.
Bibliography: p. 111-114.
usc 19/09/18
Loans
Keywords: Banks and banking; Monetary policy; Bank of England; Great Britain